If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1(6x + (8 + -1(x + 1))) = -2x + 1 Reorder the terms: 5x + -1(6x + (8 + -1(1 + x))) = -2x + 1 5x + -1(6x + (8 + (1 * -1 + x * -1))) = -2x + 1 5x + -1(6x + (8 + (-1 + -1x))) = -2x + 1 Combine like terms: 8 + -1 = 7 5x + -1(6x + (7 + -1x)) = -2x + 1 Remove parenthesis around (7 + -1x) 5x + -1(6x + 7 + -1x) = -2x + 1 Reorder the terms: 5x + -1(7 + 6x + -1x) = -2x + 1 Combine like terms: 6x + -1x = 5x 5x + -1(7 + 5x) = -2x + 1 5x + (7 * -1 + 5x * -1) = -2x + 1 5x + (-7 + -5x) = -2x + 1 Reorder the terms: -7 + 5x + -5x = -2x + 1 Combine like terms: 5x + -5x = 0 -7 + 0 = -2x + 1 -7 = -2x + 1 Reorder the terms: -7 = 1 + -2x Solving -7 = 1 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -7 + 2x = 1 + -2x + 2x Combine like terms: -2x + 2x = 0 -7 + 2x = 1 + 0 -7 + 2x = 1 Add '7' to each side of the equation. -7 + 7 + 2x = 1 + 7 Combine like terms: -7 + 7 = 0 0 + 2x = 1 + 7 2x = 1 + 7 Combine like terms: 1 + 7 = 8 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| 6(4x-4)=3(8x+3) | | m=160-15(6) | | [4x-6]=14 | | 3+16r-2=9r+78-4r | | 5(y-2)=-2(12-9y) | | (-x-1)(-6x+4)=2x*3x | | 3+16r-2=94+78-4r | | 3n+9n=96 | | 4.3-2.1t-2.3=7.6 | | .8(18+x)=7 | | 120=255-15w | | 33+15w=5+6x+9 | | .8(1+x)=7 | | 10x-5=2x+43 | | 61+2x=12x-8 | | 6x+17=4x+3 | | 8(18+x)=7 | | 2(x-2)+3=2x+2 | | 2/3=11+4x/5 | | m=255-15(6) | | .18(18+x)=7 | | 2x+5=3x+11 | | 2x*4+7=33 | | 11m-8-6m= | | 4.2q-5.2-5.2q=-2.0q-1.6 | | 3(x-1)=2x+7 | | 3x^2-16x+2=0 | | 3x^3+12x-24=0 | | 0.5(4x*x)=338 | | 7.85-2.1c=20.75 | | 7x^2+8x-4=0 | | y-27=-13 |